When Words Matter: Language Choices and Brand Building on Two Global Coffee Shop Retail Brands in Indonesia - Jovid Jonathan Latukolan; Rustono Farady Marta; Engliana Engliana (Budapest International Research and Critics University, 2021)
English is an essential element in the field of marketing communication. The use of sound and correct language can provide its image for the public to view its brand’s image. The use of foreign language itself is one form of forming a brand image so that the public or potential consumers themselves can see a brand with a more positive image. This study aims to look at the purpose of implementing language choice on the Instagram page of Starbucks Indonesia and Coffee Bean Indonesia in building the brand image of these two global coffee shop brands in Ramadan month and the Eid celebration. This study employs a qualitative approach with an interpretive research paradigm. Laura Oswald’s marketing semiotics is the analytical method used in the current study. This study indicates that Starbucks Indonesia and Coffee Bean Indonesia have different target markets and distinctive brand images. Starbucks Indonesia uses simple words and sentences. Starbucks has a more personal or individual promotion; Coffee Bean Indonesia has a more dynamic approach and has word choices that are immediately related to religion and culture; the image created by Coffee Bean itself is familiar to the Indonesians and their social environment.